Comparative Test Effort Electrocardiography - Balistocardiography - Alarcón Falcón, Humberto (1965)
One of the problems in the care of coronary patients is accurately assessing the functional state of the myocardium. Contributions from Master ( 25, 26) , using the Test of electrocardiographic Effort constitute itself a doctrinal issue in evaluating the state of coronary sufficiency. However, results based seudonegativos Scherf and Schaffer ( 33 ) can be found in 20% , and even the same Master considered by over 50 % . Recent research by Simonson (34, 35, 36 ), reviews the impact should be taken into account also in seudopositivos results. Be remembered that if a Stress Test is negative , is no guarantee for exempting imminent post coronary insufficiency ( 12). With the introduction of Practice Ballistocardiography by Dock system (10 ) , ( 11) , it is possible to insist on this method to find out the exact behavior of the myocardium in patients with coronary disease.